The Influence of Fake News, Personality of Muslim Customers and Anger Against Hateful Behavior of Muslim Consumers at Brands Halal Products With Religiosity As Moderation Variable - Warsito, Chandra; Sholikhin, Iin; Farhah, Nida Umi; Ab. Wahab, Norailis; Kurniawan, Arief Adhy; Wibisono, Dhika Dzulkarnain (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study aims to determine the role of religiosity in moderating the influence of fake news variables, the personality of Muslim customers, and anger towards the hateful behavior of Muslim consumers towards halal product brands. Primary data collection was carried out by purposive sampling with a total sample of 340 response questionnaires collected from consumers of fast food restaurant outlets (Kentucky Fried Chicken, McDonald's, and Pizza Hut) domiciled in Purwokerto, Tegal, Yogyakarta, Surakarta, and Semarang. The relationship between fake news variables, Muslim customer personality, and anger towards hateful behavior towards brands were analyzed using Structural Equation Modeling from the Warp Partial Least Squares regression program package. Empirical research shows the influence of fake news, Muslim personality, and anger on brand hatred. The test results show that religiosity can be a moderating variable between fake news, Muslim personalities, and anger towards brand hate for halal products. Hatred about the brand can be suppressed if the company provides information quickly regarding the products offered, and this news can be quickly verified through social media; the information provided is straightforward to understand, and consumers are always optimistic and able to provide good perceptions so consumers do not feel they hate food and beverages and can ensure a halal product.